PENGARUH PERUBAHAN PENGGUNAAN LAHAN TERHADAP DEBIT PUNCAK DI DAS PEUSANGAN BIREUEN : Land use - Pratiwi, Hilda; Yusdiana, Yusdiana (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2022)
The purpose of this study were to analyze and determine the magnitude of the effects of land use changes for run off coefficient and peak flows in Krueng Peusangan This study held in Krueng Peusangan, Bireuen. Land use changes in Krueng Peusangan on period 2015 - 2019 is of secondary forest decreased covers 1950 ha (2,41%), reduced mixed land farming 1241 (1,54%), ricefield 812 ha (1,00%) and the dry land agriculture 97 ha (0,12%), while the addition of comprehensive settlement of 2150 ha (2,66%), and shrubs thicket 1950 ha (2,41%) of the total area of Krueng Peusangan. Runoff coefficient value (C) increased from 0.19 in 2015 to 0.20 in 2019. Keyword: DAS, land use, runoff coefficient